Quest Narratives and Heroine Journeys: the road to freebirth and the joy of undisturbed physiological birth - McKenzie, Gemma (Frontiers in Global Women's Health, 2025)
Freebirth (intentionally giving birth without doctors or midwives present) is a taboo and stigmatised birthing decision. In this study, 16 women who had freebirthed their babies in the UK were interviewed, and the data was analysed using the voice-centred relational method (VCRM). This methodology produces a range of outputs, including I-Poetry. Previous scholars have noted the difficulty in presenting results from VCRM research and have devised varied and creative ways of subverting these obstacles. Uniquely, this article relies on the theories of Joseph Campbell, Arthur Frank, and Kim Hudson to present women's freebirth accounts as both Quest Narratives and Heroine Journeys. The article outlines the theoretical underpinnings of the Heroine’s Journey and demonstrates its use with women's freebirth accounts as they pertain to the joy of undisturbed physiological birth.